Beyond dichotomy between protection and management of marine mammals in Japan - Matsuda, Hiroyuki; Yamamura, Orio; Kitakado, Toshihide; Kobayashi, Yumi; Kobayashi, Mari; Hattori, Kaoru; Kato, Hidehiro (THERYA, 2015)
Introduction: Marine mammals are natural resources for humans. They are also considered as pests in some fisheries. Damage to fisheries by Steller sea lions in northern Japan has increased since the 1990s. The major factor that drives the relationship between humans and marine mammals has changed from the middle of the 20th century to the early 21st century; this is the result of changes in the extent to which their populations are threatened, the demand for these natural resources, and policies for marine mammal conservation. Methods: In this paper, we have chosen four major taxa of marine mammals to investigate changes in policies for marine mammals in Japan: Steller sea lions, harbor seals, dugong and cetaceans. Some cetacean species have been overexploited in the past and remain threatened. Their full recovery is still awaited. Other large cetacean species have never been threatened; nevertheless all commercial whaling was placed under a moratorium by the International Whaling Commission in 1982. Results: Japan still catches small cetaceans in coastal whaling operations and large cetaceans for scientific research. Except for cetaceans, the policy for marine mammals has changed from resource use in the middle of the 20th century, to protection in the late 20thcentury, and to nuisance control since 2014. Environmental groups played an important role in building consensus for these policy changes. Discussion and conclutions: We seek a comprehensive policy that achieves a balanced approach to accommodate three different roles of marine mammals: a natural resource, participants in marine ecosystems and agents of damage to fisheries. We also discuss the importance of stakeholder involvement in changing policies for wildlife management, ranging from complete protection to population control. Key words: Adaptive wildlife management; japanese commercial whaling; dugong, Harbor seals; population control; stakeholder involvement; steller sea lion.